Hepatotoxic effect of antifungal drugs itraconazole and fluconazole on rats - Yaacob, Azhar (2013)
Itraconazole and fluconazole are synthetic triazole antifungal from azole group. They exhibit fungistatic property by inhibiting ergosterol formation, an important structure in fungal membrane. These drugs have a broad spectrum antifungal activity and been used widely in treating Candida albicans, Aspergillus spp.,Cryptococcus neoformans and many others. Unfortunately, these drugs were reported to cause liver toxicity in patients. The objective of this study is to study the hepatotoxicity effect of itraconazole and fluconazole in rats. In vitro toxicity test was done by using liver slice toxicity test method using normal rat’s liver. Livers were harvested and sliced between 30-40 mg per slice. The liver slices were then incubated in 8 ml of complete RPMI-1640 media supplemented with itraconazole and fluconazole at different concentrations (0.0, 0.0001, 0.001, 0.01 and 0.1 mM). Incubation was done for 20, 40 and 60 minutes. After incubation was completed, liver slices were fixed in 10% formalin and prepared for hematoxylen and eosin (H&E) staining while incubation media was test for aspartate transaminase (AST) and alanine transaminase (ALT) level. H&E staining evaluation of viable hepatocytes demonstrate that only incubation with itraconazole for 60 minutes, at all four concentrations gave significant low viable hepatocytes when compared to control group. While for AST and ALT level in incubation media, both itraconazole and fluconazole cause increment in time dependent pattern. Regarding the in vitro study, the difference between these two drugs was not significant. In vivo repeated dose treatment method was also conducted in this study. Rats were divided into one control and 6 treatment groups which treated with 10, 50 and 100mg/kg itraconazole or fluconazole. 1 ml treatment was given intraperitoneally, daily for 14 days. At day 15, the rats were sacrifice and liver were processed for mitochondrial permeability test (MPT),comet assay and immunohistochemistry staining. Result for MPT test suggests that itraconazole treatment lead to mitochondrial membrane pore formation in dose and time dependent pattern. Comet assay that been done to detect DNA damage showed that itraconazole caused more DNA damage compared to fluconazole especially at 50 and 100 mg/kg dosing. Immunohistochemistry staining show that bax protein was expressed especially at the higher dose for both drugs. In conclusion, itraconazole cause more hepatotoxicity effect compared to fluconazole.